2020
DOI: 10.1021/acsabm.0c00488
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Conjugated pH and Redox-Sensitive Ellipsoidal Hybrid Magnetic Nanoparticles for Dual-Triggered Drug Release

Abstract: Stimuli-sensitive and multifunctional nanoparticles are highly desirable biomedical materials for triggered and targeted drug delivery applications. Here, we have designed pH-and redox-triggered magnetic lipid−polymer hybrid nanoparticles (MHNPs) with a core− shell structure. This design is composed of a silica-/mesoporous silicacoated ellipsoidal magnetic nanoparticle with multifunctionality: carrying the anticancer drug (doxorubicin, DOX), the cancer cell targeting ligand (folic acid-conjugated poly(ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The DOX loading efficiency (DLE) of LAP nanodisks was evaluated via the measurement of the specific UV absorption band of DOX at 480 nm using the UV–vis spectrophotometer. The DLE of DOX was calculated according to the following equation by using the standard calibration curve of DOX (Figure S2)­ …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The DOX loading efficiency (DLE) of LAP nanodisks was evaluated via the measurement of the specific UV absorption band of DOX at 480 nm using the UV–vis spectrophotometer. The DLE of DOX was calculated according to the following equation by using the standard calibration curve of DOX (Figure S2)­ …”
Section: Experimental Sectionmentioning
confidence: 99%
“…For instance, FA can stimulate cellular internalization of MNPs in active manner [ 283 ]. In vitro studies indicated FA promoted the targeted and controlled release of DOX in a dual release mechanism (pH and redox) [ 284 ] and a redox-responsive mechanism, respectively [ 283 ]. FA is cheap and widely available, has low immunogenicity and toxicity, also it is simple to alter for application as single/dual targeted systems in neoplasm treatment [ 274 , 281 ].…”
Section: Magnetic Nanoparticle Targeting Methodsmentioning
confidence: 99%
“…After incubation, free Dox, free ZnPc-N 3 , and GNPs-ZnPc/Dox were added into the wells and cells were incubated for 4 h. Analysis of at least 10000 cells for each sample was performed on a BD Accuri C6 flow cytometer. MFI determination was described in a previous study , (Figure C, D).…”
Section: Experimental Partmentioning
confidence: 99%